Electrochemically Activation of Pencil Graphite Electrode for Determination of Ascorbic Acid and Uric Acids - ARDJMAND, M.; SHOKUHI RAD, A. (Asian Journal of Chemistry, 2010)
Uric acid and ascorbic acid are very important electroactive compounds inside biological mediums such as blood and urine and their determination has significant topic. The main problem for simultaneous determination of these biological compounds is their analytical signals overlapping. In present study, the assessment of these compounds in samples is considered using electrochemically activated pencil graphite electrode. Optimum conditions to simultaneous determination of these two compounds, has taken as blow: (1) applying cyclic voltammetry method to electroactivation of pencil graphite electrode, (2) adjusting the electrolyte pH value 14 for activation of electrode to (3) applying 30 numbers of cycles to activation of electrode, (4) choosing phthalate buffer (pH = 5) to analyte determination. The obtained results show that in co-present of 9.31 × 10-4 M uric acid the anodic peak current for ascorbic acid is linear for concentration range of 2.33 × 10-5 to 3.66 × 10-3 M having the correlation coefficient of 0.9998. Detection limit for differential pulse voltammetry determination of ascorbic acid has gained 5.74 × 10-5 M.